Regioisomer‐Free Chlorinated Thiophene‐Based Ending Group for Thieno[3, 2‐b]thiophene Central Unit‐Based Acceptor Enabling Highly Efficient Nonfullerene Polymer Solar Cells with High Voc Simultaneously. Issue 1 (31st October 2019) - Ni, Shan-Shan; Xu, Xiaopeng; Wang, Jin-Liang; Wan, Shi-Sheng; Liu, Kai-Kai; Bai, Hai-Rui; Yang, Can; Lv, Guiqin; Peng, Qiang
Abstract : A pair of pure regioisomeric acceptor–donor–acceptor (A–D–A) typed nonfullerene small molecule acceptors (NF‐SMAs) (4TTIC and 4TTIC‐Cl), containing a central thieno[3, 2‐ b ]thiophene‐sp 3 hybridized "carbon‐bridge"‐based fused ring core unit and thiophene‐based IC or chlorinated thiophene‐based IC are synthesized for polymer solar cells (PSCs). Compared with 4TTIC, 4TTIC‐Cl not only achieves a red‐shifted absorption spectra and lower energy levels but also enhancement of molecular packing and crystallinity. The 4TTIC‐Cl ‐based blend films display higher and more balanced charge carrier mobilities, more favorable morphology, and more efficient exciton dissociation in comparison with the 4TTIC ‐based blend film. The optimized devices based on PBDB‐ST:4TTIC‐Cl deliver an impressively high power conversion efficiency (PCE) of 13.11% and fill factor of 74%, much higher than that of the PBDB‐ST:4TTIC ‐based devices. Moreover, a small energy loss of ≈0.54 eV and a decent V oc of 0.88 V are simultaneously achieved for PBDB‐ST:4TTIC‐Cl ‐based devices. Noticeably, the PCE of 13.11% is the highest reported value for NF‐SMAs containing the central thieno[3, 2‐ b ]thiophene unit with sp 3 hybridized carbon‐bridged cyclopentadiene fragments in binary PSCs. This study proves that introduction of less electron‐deficient thiophene‐based IC terminal group into thieno[3, 2‐ b ]thiophene central core‐based SMAs is a very effective method for making high V oc and excellent PCE simultaneously. Abstract : An effective method is proposed for excellent power conversion efficiency (PCE) with high V oc in polymer solar cells (PSCs) by introducing a weak electron‐deficient thiophene‐based IC terminal group into thieno[3, 2‐ b ]thiophene central core‐based small molecule acceptors. An excellent PCE of 13.11% with V oc of 0.88 V is obtained, which is the highest reported for A–D–A‐type nonfullerene acceptors containing the central thieno[3, 2‐ b ]thiophene unit with sp 3 hybridized carbon‐bridged cyclopentadiene fragments in binary PSCs.